Cavitation-resistant lubricating wear-resistant high-entropy alloy composite coating and preparation method thereof
By using Al-Cr-Co-Ni quaternary high-entropy alloy composite coating of Al-Cr-Co-Ni quaternary high-entropy alloy and Ag on the frictional side surface of the aviation fuel pump, the problem of difficult to take into account both cavitation resistance and lubrication and wear resistance in the prior art is solved. It achieves good protection effect under high temperature and high pressure conditions.
Patent Information
- Application Number
- CN202411580172.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-07
AI Technical Summary
The prior art is difficult to take into account both cavitation resistance and lubrication and wear resistance on the friction surface of the aviation fuel pump, resulting in severe wear and cavitation combined damage to the components under high temperature and high pressure conditions.
A uniform and dense high-entropy alloy composite coating was prepared on the surface of the metal substrate by using a mixed powder of Al-Cr-Co-Ni quaternary high-entropy alloy and Ag.
The performance of maintaining low friction coefficient, low wear rate and low cavitation quality loss in low viscosity aviation kerosene is achieved, and the wear resistance and cavitation resistance of the components are significantly improved.
Smart Images

Figure CN119411054A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of advanced metal materials and surface protection, and specifically relates to an anti-cavitation, lubricating, and wear-resistant high-entropy alloy composite coating and a preparation method thereof. Background Art
[0002] In order to further improve the thrust-to-weight ratio of aircraft engines and the combustion efficiency of fuel, the speed and load of the thrust bearing / gear friction pair of the engine fuel pump and the temperature of the oil medium in the fuel pump are constantly increasing, resulting in a decrease in the viscosity of the fuel and a deterioration in the ability to form an oil film on the surface of the components. However, the degree of cavitation becomes more severe, causing more serious wear and cavitation damage to components such as thrust bearings and gears, seriously affecting the life and operating stability of related components, and posing a potential threat to the flight safety of the aircraft.
[0003] MoS 2 Bonded solid lubricating coatings such as molybdenum-based and graphite-based coatings can significantly improve their tribological properties under oil-poor conditions when applied to the surfaces of thrust bearings and other components due to their excellent solid lubricating properties. Therefore, they have been widely studied and used in the United States, Russia and my country (CN112251135A). However, with the continuous increase in fuel pump speed and oil temperature, the protective effect of such coatings has been significantly deteriorated, and large pieces of flaking caused by cavitation often occur, which in turn affects the friction reduction and wear resistance effect. The reason is that bonded solid lubricating coatings usually use organic resins as binders, which have poor mechanical strength and temperature resistance. It is difficult to resist the high-frequency impact and high-temperature burning caused by the collapse of tens of thousands of bubbles formed by oil cavitation, and they are prone to cracking, melting and carbonization (China Surface Engineering., 2024, 37(5), 1-14); in addition, MoS 2 Graphite is an inorganic material with quite different properties from organic resins. The interface bonding between the two is poor, and the deformation response under external force is significantly different, so it is also easy to produce interface cracking and peeling. The existence of these problems greatly limits the improvement of fuel pump performance, and it is urgent to develop a new surface coating that takes into account both anti-cavitation and lubrication and wear resistance.
[0004] The invention patent "Anti-cavitation-corrosion high-entropy alloy coating and its preparation method" with publication number CN115418595B discloses an Al-Cr-Co-Ni series high-entropy alloy coating, which has a relatively high work hardening index and plastic deformation work, and exhibits a relatively excellent ability to absorb bubble collapse impact energy, and is also resistant to seawater corrosion, so it is suitable for use as an anti-cavitation-corrosion coating in marine environments. However, due to the lack of sufficient solid lubrication properties, the coating has poor wear resistance in low-viscosity aviation kerosene, especially under high-speed and high-load conditions where the surface of the component is depleted of oil, so the coating cannot be used as a protective coating on the friction surface of the fuel pump.
[0005] Since it is difficult to achieve both anti-cavitation and lubrication and wear-resistant properties, there has been no public report on anti-cavitation, lubrication and wear-resistant coatings suitable for aviation fuel pumps at home and abroad. Summary of the invention
[0006] In view of the problems existing in the above-mentioned background technology, the present invention discloses an anti-cavitation, lubricating and wear-resistant high-entropy alloy coating and a preparation method thereof. The coating is suitable for the working environment of the friction pair of an aircraft engine fuel pump and can maintain a low friction coefficient, wear rate and cavitation mass loss in low-viscosity aviation kerosene.
[0007] The technical solution adopted by the present invention is as follows: A method for preparing a cavitation-resistant, lubricating, and wear-resistant high-entropy alloy composite coating comprises the following steps: (1) Weighing Al-Cr-Co-Ni quaternary high entropy alloy powder and Ag powder respectively according to mass percentage, placing the powders in a mechanical mixer and mixing them uniformly to obtain spray powder; (2) drying the spray powder obtained in step (1) and loading it into a powder feeder of a spraying device for standby use; (3) The surface of the metal substrate is roughened by sandblasting and cleaned, and then fixed on a spraying table; (4) After setting the spraying process parameters, start the thermal spraying equipment, send the powder into the flame flow and spray and deposit it on the surface of the metal substrate to obtain an anti-cavitation, lubricating and wear-resistant high-entropy alloy composite coating.
[0008] Preferably, the Al-Cr-Co-Ni quaternary high entropy alloy powder and the Ag powder in step (1) are spherical or nearly spherical in shape, and have a particle size range of 5 to 100 μm.
[0009] Further preferably, in step (1), the mass percentage of the Al-Cr-Co-Ni quaternary high entropy alloy powder is 80.00-95.00%, and the mass percentage of the Ag powder is 5.00-20.00%.
[0010] More preferably, the atomic ratio of each element in the Al-Cr-Co-Ni quaternary high entropy alloy powder in step (1) is Al 7.6~15%, Cr 21~30%, Co 20~29%, Ni 31~40%; for the specific preparation steps, refer to Chinese invention patent CN202210997311.4.
[0011] Preferably, the drying temperature in step (2) is 80-120° C., and the fluidity of the powder after drying is 10-25 s / 50 g.
[0012] Preferably, in step (3), the metal substrate is copper alloy, titanium alloy, aluminum alloy, stainless steel, etc., and the roughness of the surface of the metal substrate after sandblasting is ≥1 μm.
[0013] Preferably, the thermal spraying equipment in step (4) is a supersonic flame spraying equipment, the fuel gas used is natural gas or kerosene, the supporting fuel gas is oxygen or air, and the carrier gas is nitrogen, argon or helium.
[0014] Further preferably, the spraying parameters in step (4) are spraying distance 25-32 cm, gun moving speed 200-2000 mm / s, distance between spraying sprays 1-4 mm, powder feeding rate 10-80 g / min, compressed air pressure 100-120 MPa, compressed air flow rate 18-22 m 3 / h, oxygen pressure 160~180MPa, oxygen flow rate 19~23m 3 / h, gas pressure 120~140MPa, gas flow 15~19m 3 / h.
[0015] Further preferably, the thickness of the coating deposited in step (4) is 50-1000 μm.
[0016] The present invention uses a mixed powder of Al-Cr-Co-Ni quaternary high entropy alloy and Ag with a single face-centered cubic structure (FCC) with the same crystal structure of (111) crystal plane preferred orientation as a spray feed, and uses a supersonic flame spraying technology with a flame velocity of up to 7-8 Mach to deposit and prepare a high entropy alloy composite coating on the surface of a metal substrate. The obtained coating not only has a uniform and dense structure, but also well retains the original phases and crystal structures of the two powders. Because the two metals have good temperature resistance and the same crystal structure, their properties are very similar, and their response behaviors under external forces are more matched: under the action of friction, the rich slip system in the FCC phase can easily drive the crystal plane to slip, especially the solid lubricating phase Ag with good ductility, so it is easy to form a continuous lubricating film on the friction interface; under the impact of bubble collapse, the Al-Cr-Co-Ni quaternary high entropy alloy and Ag can absorb the impact energy through plastic deformation to prevent interface cracking and material peeling. Therefore, the high entropy alloy composite coating of the present invention has the functions of lubrication, wear resistance and cavitation resistance, has good protection ability in the working environment where cavitation and wear exist simultaneously, and is suitable for application to the surface of mechanical parts such as aircraft engine fuel pumps. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The SEM morphology and XRD spectrum of the sprayed powder of Example 1 are shown.
[0018] Figure 2The SEM cross-sectional morphology, EDS surface distribution diagram of the Ag element and the XRD spectrum of the high entropy alloy composite coating prepared by the supersonic flame spraying technology in Example 1.
[0019] Figure 3 1 is the load-displacement curve of the high entropy alloy powder and the high entropy alloy component in the composite coating of Example 1.
[0020] Figure 4 The high entropy alloy composite coating prepared in Example 1 and the MoS prepared in Comparative Example 3 2 Surface SEM morphology of graphite-based bonded solid lubricating coating after friction and wear test in RP-3 aviation kerosene.
[0021] Figure 5 The high entropy alloy composite coating prepared in Example 1 and the MoS prepared in Comparative Example 3 2 Surface SEM morphology of graphite-based bonded solid lubricating coating after cavitation test in RP-3 aviation kerosene for 1 hour.
[0022] Figure 6 The high entropy alloy composite coatings and MoS prepared in Examples 1 to 3 and Comparative Examples 1 to 3 2 Bonded solid lubricating coating and MoS 2 Friction coefficient and cavitation cumulative mass loss curve of graphite-based bonded solid lubricating coating in RP-3 aviation kerosene. DETAILED DESCRIPTION
[0023] The present invention will be further explained below in conjunction with the embodiments.
[0024] Example 1 (1) Al-Cr-Co-Ni high entropy alloy powder and Ag powder are selected as raw materials, and the weight percentages are 90wt% and 10wt%, respectively. The particle size range of the two powders is 15-53μm, and the atomic percentages of each element in the Al-Cr-Co-Ni high entropy alloy powder are: Al 10.00%, Cr 28.00%, Co 28.00%, Ni 34.00%. The above ingredients are placed in a mechanical mixer and mixed evenly to obtain a spray powder; (2) Place the above spray powder in an oven, bake at 100°C for 1 hour, and then load it into the powder feeder of the spray equipment for standby use; (3) Use copper alloy as the metal substrate, use a sandblasting machine to roughen its surface to a roughness of ≥1 μm, then clean it with acetone and fix it on the spraying table; (4) The spraying process parameters of the supersonic flame spraying equipment are set as follows: spraying distance is 27.5 cm, pass spacing is 2 mm, gun moving speed is 800 mm / s, powder feeding rate is 25 g / min, air pressure is 110 MPa, and air flow rate is 19.0 m 3 / h, oxygen pressure is 170MPa, oxygen flow rate is 20.4m 3 / h, natural gas pressure is 130MPa, natural gas flow rate is 16.6m 3 / h, start the spraying equipment, send the powder into the flame flow and spray and deposit it on the surface of the copper alloy substrate to obtain an anti-cavitation, lubricating, and wear-resistant high-entropy alloy composite coating with a coating thickness of about 500μm; (5) The MMW-1 vertical universal friction and wear testing machine with end face contact was used to simulate the contact mode of the fuel pump thrust bearing / gear friction pair to characterize the friction and wear performance of the coating prepared in step (4) at room temperature, 20N, and 200r / min. The dual material was a pin with a diameter of 5mm made of 2Cr3WMoV, the actual material used for fuel pump gears. The test results are shown in Table 1. The coating exhibits better lubrication and wear resistance than the existing bonded solid lubricant coating. (6) The cavitation mass loss of the high entropy alloy composite coating prepared in step (4) in RP-3 aviation kerosene was tested using an ultrasonic vibration cavitation tester. The results showed that the cumulative mass loss after cavitation for 10 hours was significantly less than that of the existing bonded solid lubricant coating, see Figure 6 , combined with the result of step (5), the coating shows very good anti-cavitation lubrication and wear resistance.
[0025] Example 2 (1) Al-Cr-Co-Ni high entropy alloy powder and Ag powder were selected as raw materials, and the weight percentages were 94wt% and 6wt%, respectively. The particle size range of the two powders was 15-53μm. The weight percentages of the elements in the Al-Cr-Co-Ni high entropy alloy powder were: Al 10.00%, Cr 28.00%, Co 28%, and Ni 34%. The above ingredients were placed in a mechanical mixer and mixed evenly to obtain a spray powder.
[0026] (2) Place the above spray powder in an oven, bake at 110°C for 1 hour, and then load it into the powder feeder of the spray equipment for standby use; (3) Use stainless steel as the metal substrate, use a sandblasting machine to roughen its surface to a roughness of ≥1 μm, then clean it with petroleum ether and fix it on the spraying table; (4) The spraying process parameters of the supersonic flame spraying equipment are set as follows: spraying distance is 27.5 cm, pass spacing is 2 mm, gun moving speed is 800 mm / s, powder feeding rate is 25 g / min, air pressure is 110 MPa, and air flow rate is 19.0 m 3 / h, oxygen pressure is 170MPa, oxygen flow rate is 20.4m 3 / h, natural gas pressure is 130MPa, natural gas flow rate is 16.6m 3 / h, start the spraying equipment, send the powder into the flame flow and spray and deposit it on the surface of the stainless steel substrate to obtain an anti-cavitation, lubricating and wear-resistant high-entropy alloy composite coating with a coating thickness of about 400μm; (5) The MMW-1 vertical universal friction and wear testing machine with end face contact was used to simulate the contact mode of the fuel pump thrust bearing / gear friction pair to characterize the friction and wear performance of the coating prepared in step (4) at room temperature, 20N, and 200r / min. The dual material was a pin with a diameter of 5mm made of 2Cr3WMoV, the actual material used for fuel pump gears. The test results are shown in Table 1. The coating exhibits better lubrication and wear resistance than the existing bonded solid lubricant coating. (6) The cavitation mass loss of the high entropy alloy composite coating prepared in step (4) in RP-3 aviation kerosene was tested using an ultrasonic vibration cavitation tester. The results showed that the cumulative mass loss after cavitation for 10 hours was significantly less than that of the existing bonded solid lubricant coating, see Figure 6 , combined with the result of step (5), the coating shows very good anti-cavitation lubrication and wear resistance.
[0027] Example 3 (1) Al-Cr-Co-Ni high entropy alloy powder and Ag powder were selected as raw materials, and the weight percentages were 86wt% and 14wt% respectively. The particle size of the two powders was 15-53μm. The weight percentages of the elements in the Al-Cr-Co-Ni high entropy alloy powder were: Al 10.00%, Cr 28.00%, Co 28%, and Ni 34%. The above ingredients were placed in a mechanical mixer and mixed evenly to obtain a spray powder; (2) Place the above spray powder in an oven, bake at 100°C for 1.5 hours, and then load it into the powder feeder of the spray equipment for standby use; (3) Use stainless steel as the metal substrate, use a sandblasting machine to roughen its surface to a roughness of ≥1 μm, then clean it with acetone and fix it on the spraying table; (4) The spraying process parameters of the supersonic flame spraying equipment are set as follows: spraying distance is 27.5 cm, pass spacing is 2 mm, gun moving speed is 800 mm / s, powder feeding rate is 25 g / min, air pressure is 110 MPa, and air flow rate is 19.0 m3 / h, oxygen pressure is 170MPa, oxygen flow rate is 20.4m 3 / h, natural gas pressure is 130MPa, natural gas flow rate is 16.6m 3 / h, start the spraying equipment, send the powder into the flame flow and spray and deposit it on the surface of the stainless steel substrate to obtain an anti-cavitation, lubricating and wear-resistant high-entropy alloy composite coating with a coating thickness of about 350μm; (5) The MMW-1 vertical universal friction and wear testing machine with end face contact was used to simulate the contact mode of the fuel pump thrust bearing / gear friction pair to characterize the friction and wear performance of the coating prepared in step (4) at room temperature, 20N, and 200r / min. The dual material was a pin with a diameter of 5mm made of 2Cr3WMoV, the actual material used for fuel pump gears. The test results are shown in Table 1. The coating exhibits better lubrication and wear resistance than the existing bonded solid lubricant coating. (6) The cavitation mass loss of the high entropy alloy composite coating prepared in step (4) in RP-3 aviation kerosene was tested using an ultrasonic vibration cavitation tester. The results showed that its cumulative mass loss after cavitation for 10 h was significantly less than that of the existing bonded solid lubricant coating, see Figure 6 , combined with the result of step (5), the coating shows very good anti-cavitation lubrication and wear resistance.
[0028] Comparative Example 1 (1) Al-Cr-Co-Ni high entropy alloy powder and Ag powder are selected as raw materials, and the weight percentages are 98wt% and 2wt% respectively. The particle size range of the two powders is 15~53μm. The weight percentages of the elements in the Al-Cr-Co-Ni high entropy alloy powder are: Al 10.00%, Cr 28.00%, Co 28%, Ni 34%. The above ingredients are placed in a mechanical mixer and mixed evenly to obtain a spray powder; (2) Place the above spray powder in an oven, bake at 100°C for 1 hour, and then load it into the powder feeder of the spray equipment for standby use; (3) Use stainless steel as the metal substrate, use a sandblasting machine to roughen its surface to a roughness of ≥1 μm, then clean it with acetone and fix it on the spraying table; (4) The spraying process parameters of the supersonic flame spraying equipment are set as follows: spraying distance is 27.5 cm, pass spacing is 2 mm, gun moving speed is 800 mm / s, powder feeding rate is 25 g / min, air pressure is 110 MPa, and air flow rate is 19.0 m 3 / h, oxygen pressure is 170MPa, oxygen flow rate is 20.4m 3 / h, natural gas pressure is 130MPa, natural gas flow rate is 16.6m 3 / h, start the spraying equipment, send the powder into the flame flow and spray and deposit it on the surface of the stainless steel substrate to obtain a composite coating with a coating thickness of about 400μm; (5) The MMW-1 vertical universal friction and wear testing machine with end face contact was used to simulate the contact mode of the fuel pump thrust bearing / gear friction pair to characterize the friction and wear performance of the coating prepared in step (4) at room temperature, 20N, and 200r / min. The dual material was a pin with a diameter of 5mm made of 2Cr3WMoV, which is actually used for fuel pump gears. The test results are shown in Table 1. The coating exhibited poor friction and wear performance, and the friction coefficient and wear rate were significantly higher than those of the high entropy alloy composite coating of the present invention. This shows that even if the high entropy alloy and Ag used in preparing the composite coating are the same as those of the present invention, the tribological performance of the coating will be significantly deteriorated when the ratio exceeds the range specified in the present invention. (6) The cavitation mass loss of the composite coating prepared in step (4) in RP-3 aviation kerosene was tested using an ultrasonic vibration cavitation tester. The results showed that the cumulative mass loss after cavitation for 10 hours was small, see Figure 6 , combined with the result of step (5), although the coating has strong anti-cavitation performance, it does not have good lubrication and wear resistance.
[0029] Comparative Example 2 (1) 1.5 g of epoxy resin and 20.0 g of polyamide-imide were added to 67.7 g of a mixed solvent (75 vol % of N,N-dimethylformamide and 25 vol % of 1-methyl-2-pyrrolidone), and the mixture was stirred to completely dissolve to obtain a resin system. Then, 10.8 g of MoS 2 , and then stirred evenly to obtain MoS 2 Base bonding solid lubricating coating; (2) Stainless steel is used as the metal substrate. In order to enhance the bonding strength between the coating and the metal substrate, the surface is roughened using a sandblasting machine so that the rust removal standard level reaches at least Sa 2.5. It is then cleaned with acetone and fixed on the sample table. (3) Load the coating of step (1) into a Sterling brand spray gun, and use the Sterling brand spray gun to evenly spray the coating on the surface of the metal substrate, using a method of multiple small sprayings, and wait for the surface of the previous spray to dry before spraying the next time, until the desired thickness is reached; (4) After the sample sprayed in step (3) was left to dry at room temperature, it was placed in an oven and cured at 170°C for 60 minutes. The thickness of the coating was measured by a Mini Test 1100 eddy current thickness gauge to be approximately 22 μm. (5) The MMW-1 vertical universal friction and wear testing machine with end face contact was used to simulate the contact mode of the fuel pump thrust bearing / gear friction pair to characterize the friction and wear performance of the coating prepared in step (4) at room temperature, 20N, and 200r / min. The dual material was a pin with a diameter of 5mm made of 2Cr3WMoV, which is the actual material used for the fuel pump gear. The test results are shown in Table 1. The coating exhibited good lubrication performance, but its wear resistance was significantly inferior to that of the high entropy alloy composite coating of the present invention (Examples 1, 2, and 3). (6) The cavitation mass loss of the coating prepared in step (4) in RP-3 aviation kerosene was tested using an ultrasonic vibration cavitation tester. The results showed that the cumulative mass loss after cavitation for 10 hours was significantly greater than that of the high entropy alloy composite coating of the present invention (Examples 1, 2, and 3). Figure 6 , combined with the result of step (5), although the coating has good lubrication performance, it does not have good wear resistance and cavitation resistance.
[0030] Comparative Example 3 (1) First, 64.2 g of a mixed solvent was prepared at a ratio of 75 vol% of N,N-dimethylformamide and 25 vol% of 1-methyl-2-pyrrolidone. Then, 25.0 g of polyamide-imide was added to part of the mixed solvent and stirred to completely dissolve it to obtain a resin system. Then, 8.1 g of MoS 2 2.7 g of graphite was put into a ball mill, and then a mixed solvent of 1 to 2 times the total weight of the mixed material was added. After grinding for 48 hours, the dispersed material was obtained. Finally, the dispersed material and the remaining solvent were added to the resin system and stirred evenly to obtain MoS 2 / Graphite-based bonded solid lubricating coating; (2) Stainless steel is used as the metal substrate. In order to enhance the bonding strength between the coating and the metal substrate, the surface is roughened using a sandblasting machine so that the rust removal standard level reaches at least Sa 2.5. It is then cleaned with acetone and fixed on the sample table. (3) Load the coating of step (1) into a Sterling brand spray gun, and use the Sterling brand spray gun to evenly spray the coating on the surface of the metal substrate, using a method of multiple small sprayings, and wait for the surface of the previous spray to dry before spraying the next time, until the desired thickness is reached; (4) After the sample sprayed in step (3) is left to dry at room temperature, it is placed in an oven and cured at 280°C for 60 minutes. The thickness of the coating is measured by a Mini Test 1100 eddy current thickness gauge to be approximately 25 μm; (5) The MMW-1 vertical universal friction and wear testing machine with end face contact was used to simulate the contact mode of the fuel pump thrust bearing / gear friction pair to characterize the friction and wear performance of the coating prepared in step (4) at room temperature, 20N, and 200r / min. The dual material was a pin with a diameter of 5mm made of 2Cr3WMoV, which is the actual material used for fuel pump gears. The test results are shown in Table 1. The coating exhibited good lubrication performance, but its wear resistance was not as good as the high entropy alloy composite coating of the present invention (Examples 1, 2, and 3); (6) The cavitation mass loss of the coating prepared in step (4) in RP-3 aviation kerosene was tested using an ultrasonic vibration cavitation tester. The results showed that the cumulative mass loss after cavitation for 10 hours was significantly greater than that of the high entropy alloy composite coating of the present invention (Examples 1, 2, and 3). Figure 6 , combined with the result of step (5), although the coating has good lubrication performance, it does not have good wear resistance and cavitation resistance.
[0031] Performance testing and data analysis: (1) Coating structure Taking the spraying powder and high entropy alloy composite coating prepared in Example 1 as an example, the morphology and phase composition of the spraying powder and coating prepared in the present invention were analyzed using a scanning electron microscope (SEM) and an X-ray diffractometer (XRD).
[0032] Figure 1 The SEM morphology and XRD spectrum of the sprayed powder. It can be seen that the powder has good sphericity and the particle size range is mainly distributed in the range of 15~53μm, indicating that it has good fluidity. The characteristic peaks of Al-Cr-Co-Ni high entropy alloy and Ag can be clearly observed in the XRD spectrum, showing that the crystal structure of both is a single FCC phase, and (111) is its preferred orientation crystal plane.
[0033] Figure 2The SEM cross-sectional photo, EDS surface distribution diagram of Ag element and XRD spectrum of the high entropy alloy composite coating prepared by supersonic flame spraying process are given. It can be seen that the coating is very dense, and there is almost no obvious pore defect inside. The thickness of the coating is about 500μm, and it is very tightly bonded to the interface of the substrate; in addition, Ag is very evenly distributed and exists independently in the composite coating, and is not dissolved into the crystal structure of the high entropy alloy, which shows that the present invention can obtain a composite coating with uniform and dense structure without destroying the original phase of the powder by spraying the mixed powder by supersonic flame spraying process. The XRD spectrum of the coating also confirms the above results. The peak positions and intensities of the characteristic peaks of the two components in the spectrum are almost exactly the same as those of the sprayed powder, which shows that the preparation process of the present invention can indeed preserve the original phase and crystal structure of the sprayed powder in the composite coating, which is conducive to the coating to maintain good lubrication, wear resistance and anti-cavitation properties during friction and cavitation.
[0034] (2) Coating performance test In order to better study the performance of the high entropy alloy composite coating of the present invention, a nanoindenter was used to detect the changes in the mechanical properties of the high entropy alloy powder and the high entropy alloy components in the coating. The results are as follows Figure 3 As shown, the original nanohardness and elastic modulus of the high entropy alloy powder are as high as 4.937 GPa and 101.995 GPa, respectively, which is mainly due to the strengthening effect brought by the unique lattice distortion effect of the high entropy alloy; compared with the powder, the mechanical properties of the high entropy alloy component in the coating of Example 1 are further improved, and the nanohardness and elastic modulus are 6.855 GPa and 212.653 GPa, respectively. This is because the high entropy alloy is an FCC phase with many slip systems, and it is easy to generate strengthening structures such as dislocations and twins during the process of spraying and high-speed impact on the surface of the substrate, indicating that the high entropy alloy matrix in the composite coating of the present invention also has the effect of self-strengthening, which is conducive to better improving the bearing capacity, impact resistance and wear resistance of the coating.
[0035] The friction and wear test of the four coatings of Example 1 and Comparative Examples 1 to 3 was carried out in RP-3 aviation kerosene using an MMW-1 vertical universal friction and wear tester according to ASTM G99-17 standard. The test conditions were: room temperature, RP-3 aviation kerosene medium, load of 20N, rotation speed of 200r / min, and friction time of 14400s. The test results are shown in Table 1 and Figure 6 As shown: Table 1 High entropy alloy composite coatings and MoS prepared in Examples 1 to 3 and Comparative Examples 1 to 3 2 Bonded solid lubricating coating and MoS 2 Friction coefficient and wear rate of graphite-based bonded solid lubricating coatings in RP-3 aviation kerosene.
[0036] As shown in Table 1, the friction coefficient of the composite coating of Example 1 is about 0.10, the wear rate is almost zero, and even slightly "negative wear" occurs; the friction coefficient of the composite coating of Comparative Example 1 is about 0.21, and the wear rate is 1.85×10 -3 mm 3 / Nm, the lubrication and wear resistance are significantly worse than those of Example 1; the friction coefficient of the coating in Comparative Example 2 is about 0.12, and the wear rate is 3.77×10 -6 mm 3 / Nm, the lubrication and wear resistance are also worse than those of Example 1; the friction coefficient of the coating of Comparative Example 3 is about 0.11, and the wear rate is 2.57×10 -6 mm 3 / Nm, and the lubrication and wear resistance are also worse than those in Example 1.
[0037] SEM was used to observe the high entropy alloy composite coating and MoS 2 Surface morphology of graphite-based bonded solid lubricating coating after friction test in RP-3 medium, such as Figure 4 As shown in the figure, the wear scar surface of the composite coating prepared in Example 1 forms a continuous shear lubrication film without obvious brittle peeling characteristics. This is due to the fact that all components in the composite coating are FCC structures with (111) crystal plane preferential orientation, which are easier to spread along the friction track under the action of friction force. On the other hand, it is due to the strong bearing capacity of the Al-Cr-Co-Ni high entropy alloy matrix. In addition, the "coking" phenomenon of aviation kerosene on the wear scar surface occurs in some areas, which is the reason for the slight "negative wear" of the coating. The MoS 2 The wear scar surface of the graphite-based bonded solid lubricant coating showed a scaly layered structure and local cracking and peeling, indicating that the MoS in the coating 2 Graphite can also slip under the action of friction shear stress, so the lubrication performance is acceptable, but the poor mechanical properties of organic resins lead to low load-bearing and tear resistance capabilities, so the wear resistance is not as good as the composite coating of the present invention.
[0038] The cavitation test of the four coatings was carried out in RP-3 aviation kerosene using an ultrasonic vibration cavitation tester in accordance with GB / T 6383-2009 standard. The test conditions were as follows: the temperature of the aviation kerosene was (25±2)°C, the vibration frequency of the horn was 20kHz, the amplitude was 50μm (peak-to-peak), the distance between the lower end of the horn and the coating surface was 0.5mm, and the distance between the sample surface and the liquid surface was 12mm. The high entropy alloy composite coating of Example 1 and the MoS composite coating of Comparative Example 3 were observed using SEM. 2 Surface SEM morphology of graphite-based bonded solid lubricating coating after cavitation in RP-3 aviation kerosene for 1 hour. Figure 5As shown, MoS 2 / The surface peeling and damage of the graphite-based bonded solid lubricating coating is very serious. This is mainly because the mechanical strength and temperature resistance of the organic resin in the coating are poor, and it cannot resist the mechanical impact and high temperature caused by the collapse of bubbles. At the same time, the properties of the organic resin and the inorganic filler in the coating are quite different, and the deformation is not coordinated under the action of external force, and cracking and peeling of the phase boundaries are prone to occur; while the damage degree of the cavitation surface of the high-entropy alloy composite coating is much lighter, indicating that the anti-cavitation, lubricating and wear-resistant high-entropy alloy composite coating of the present invention can better resist the impact damage of cavitation loads because the two metal components have good temperature resistance, the deformation behavior under the action of external force is relatively consistent, and the energy absorption capacity is good.
[0039] Use a 1 / 10,000 balance to weigh the cumulative mass loss of the sample after different cavitation times. The results are shown in Figure 6 It is not difficult to find that the cumulative mass loss of the high entropy alloy composite coating in Example 1 after cavitation in RP-3 for 10 h is only 0.4 mg, which is significantly less than that of the MoS 2 Bonded solid lubricating coating and MoS 2 / Graphite-based bonded solid lubricating coatings of 11.1mg and 11.2mg show very good anti-cavitation lubrication and wear resistance.
[0040] In summary, the present invention selects a mixed powder of Al-Cr-Co-Ni quaternary high entropy alloy and Ag with the same crystal structure as the spraying powder, and uses supersonic flame spraying technology to prepare a uniform and dense high entropy alloy composite coating on the surface of the metal substrate, which not only avoids the problem of poor impact resistance and high temperature resistance caused by the use of organic resins in the prior art bonding solid lubricating coating, but also eliminates the problem of inconsistent and mismatched responses to external forces due to the obvious differences in the properties of organic and inorganic multi-phases. Under the working conditions where cavitation and sliding wear coexist, the high entropy alloy composite coating of the present invention can not only absorb impact energy through uniform plastic deformation and greatly extend the life of cavitation resistance, but also the single FCC phase structure of the coating, especially the more ductile Ag, can also reduce the friction coefficient through shear slip. In addition, the inherent lattice distortion effect of the high entropy alloy and the self-strengthening effect generated during the spraying process, its wear resistance is also outstanding. Compared with the existing MoS 2 Compared with bonded solid lubricating coatings such as graphite-based and graphite-based coatings, the high-entropy alloy composite coating of the present invention not only has better lubrication performance, but also has improved wear resistance and cavitation resistance by dozens to hundreds of times. Therefore, it can provide more significant comprehensive protection for friction pairs such as thrust bearings / gears, and is expected to greatly improve the life, stability and work efficiency of important components such as aircraft engine fuel pumps.
Claims
1. A method for preparing a cavitation-resistant, lubricating, and wear-resistant high-entropy alloy composite coating, characterized in that: The following steps are involved: (1) Weighing Al-Cr-Co-Ni quaternary high entropy alloy powder and Ag powder respectively according to mass percentage, and mixing the powders in a mechanical mixer to obtain spray powder; (2) drying the spray powder obtained in step (1) and loading it into a powder feeder of a spraying device for standby use; (3) The surface of the metal substrate is roughened by sandblasting and cleaned, and then fixed on a spraying table; (4) After setting the spraying process parameters, start the thermal spraying equipment, send the powder into the flame flow and spray and deposit it on the surface of the metal substrate to obtain an anti-cavitation, lubricating and wear-resistant high-entropy alloy composite coating.
2. The method for preparing a cavitation-resistant, lubricating, and wear-resistant high-entropy alloy composite coating according to claim 1, characterized in that: The Al-Cr-Co-Ni quaternary high entropy alloy powder and the Ag powder in step (1) are spherical or nearly spherical in shape, and the particle size ranges from 5 to 100 μm.
3. The method for preparing a cavitation-resistant, lubricating, and wear-resistant high-entropy alloy composite coating according to claim 1, characterized in that: In step (1), the mass percentage of Al-Cr-Co-Ni quaternary high entropy alloy powder is 80.00-95.00%, and the mass percentage of Ag powder is 5.00-20.00%.
4. The method for preparing a cavitation-resistant, lubricating, and wear-resistant high-entropy alloy composite coating according to claim 1, characterized in that: In step (1), the atomic ratio of each element in the Al-Cr-Co-Ni quaternary high entropy alloy powder is Al 7.6-15%, Cr 21-30%, Co 20-29%, and Ni 31-40%.
5. The method for preparing a cavitation-resistant, lubricating, and wear-resistant high-entropy alloy composite coating according to claim 1, characterized in that: The drying temperature in step (2) is 80-120° C., and the fluidity of the powder after drying is 10-25 s / 50 g.
6. The method for preparing a cavitation-resistant, lubricating, and wear-resistant high-entropy alloy composite coating according to claim 1, characterized in that: In step (3), the metal substrate is one of copper alloy, titanium alloy, aluminum alloy or stainless steel, and the roughness of the surface of the metal substrate after sandblasting is Ra≥1μm.
7. The method for preparing a cavitation-resistant, lubricating, and wear-resistant high-entropy alloy composite coating according to claim 1, characterized in that: In step (4), the thermal spraying equipment is a supersonic flame spraying equipment, the fuel gas used is natural gas or kerosene, the auxiliary fuel gas is oxygen or air, and the carrier gas is nitrogen, argon or helium.
8. The method for preparing a cavitation-resistant, lubricating, and wear-resistant high-entropy alloy composite coating according to claim 1, characterized in that: The spraying parameters in step (4) are spraying distance 25~32cm, gun moving speed 200~2000mm / s, distance between spraying 1~4mm, powder feeding rate 10~80g / min, compressed air pressure 100~120MPa, compressed air flow rate 18~22m 3 / h, oxygen pressure 160~180MPa, oxygen flow rate 19~23m 3 / h, gas pressure 120~140MPa, gas flow 15~19m 3 / h.
9. The method for preparing a cavitation-resistant, lubricating, and wear-resistant high-entropy alloy composite coating according to claim 1, characterized in that: The thickness of the coating deposited in step (4) is 50-1000 μm.
10. An anti-cavitation, lubricating, and wear-resistant high-entropy alloy composite coating prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
High-strength long-life solid lubricating coating for main fuel pump of aero-engine
CN112251135A
A high-entropy alloy coating resistant to cavitation erosion and corrosion and its preparation method
CN115418595B
AlCoCrFeNi high-entropy alloy coating
CN114032489A
Anti-cavitation composite coating and preparation method thereof
CN114231882A
Preparation method of CoCrCuMoNi-based high-entropy alloy high-temperature self-lubricating wear-resistant coating
CN115029696A